Comparing the effects of conscious monitoring and conscious control on motor performance. (May 2017) - van Ginneken, Wouter F.; Poolton, Jamie M.; Masters, Richard S.W.; Capio, Catherine M.; Kal, Elmar C.; van der Kamp, John
Abstract: We compared the effects of conscious monitoring and control on motor performance. Participants were instructed to adopt an internal or external focus of attention in different blocks of a darts task. For one group, the internal as well as external focus instructions emphasized monitoring. For another group, the instructions emphasized control in the two focus conditions. Furthermore, participants' propensity for monitoring and control was gauged via two factors of the Movement Specific Reinvestment Scale (MSRS) (Masters, Eves, & Maxwell, 2005). These factors were Movement Self-Consciousness (MS-C) and Conscious Motor Processing (CMP), which measure propensity for conscious monitoring and control, respectively. Performance differences between the internal and external focus blocks were expressed as mean radial error (MRE). Results revealed a 3-way interaction between CMP, instruction type (monitoring versus control) and an order effect. Only in the conscious control-group, but not the conscious monitoring-group was there a 2-way interaction between CMP and order. In the conscious control-group, participants with high CMP scores showed worse performance in whichever focus block (internal or external) was presented last. There were no significant effects in the monitoring-group or of MS-C. These findings indicate that conscious control has a stronger effect on motor performance than conscious monitoring. Highlights: Attention to movement execution affects motor performance. Attention to movement execution can be divided into conscious monitoring and conscious control. Conscious control is more strongly associated with motor performance compared to conscious monitoring.